2017
DOI: 10.1037/pag0000196
|View full text |Cite
|
Sign up to set email alerts
|

Age and personal values: Similar value circles with shifting priorities.

Abstract: This study examined the relationship of personal values to age using data from two representative surveys. We hypothesized that individuals organize personal values, regardless of their age, as a circle with the same order of values on this circle but that older persons are closer to conservation and more remote from openness to change and closer to self-transcendence and more distant from self-enhancement. The structural stability of the value circle over age was largely confirmed across and within individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
(35 reference statements)
3
14
0
3
Order By: Relevance
“…7 are the discriminant of gender (females are more at the bottom of the plot; significant separation of genders on this line by t test) and the line that optimally represents the age distribution of the sample (dashed line, with older persons more towards the right of the plot; inserted scale correlates with .50 with the external age variable). The two inserted lines correspond to what has been found before with respect to gender and age (Schwartz & Rubel, 2005;Borg et al, 2017c) which supports the validity of the solution. Figure 8 shows the stress contributions of individuals and of values.…”
Section: Joint Mds Of Irvs and Pvq Indexessupporting
confidence: 86%
See 1 more Smart Citation
“…7 are the discriminant of gender (females are more at the bottom of the plot; significant separation of genders on this line by t test) and the line that optimally represents the age distribution of the sample (dashed line, with older persons more towards the right of the plot; inserted scale correlates with .50 with the external age variable). The two inserted lines correspond to what has been found before with respect to gender and age (Schwartz & Rubel, 2005;Borg et al, 2017c) which supports the validity of the solution. Figure 8 shows the stress contributions of individuals and of values.…”
Section: Joint Mds Of Irvs and Pvq Indexessupporting
confidence: 86%
“…The obvious hypothesis is that the PVQ scale fits better to the value circle theory, and the IVRS fits better to the value dimensions theory, because the scales have been developed out of these theories. Previous research (Bilsky & Hermann, 2016;Borg et al, 2017bBorg et al, , 2017c has shown that the IRVS fits well into the value circle framework. What has not been tested is whether the PVQ fits into Klages' value dimensions.…”
Section: Introductionmentioning
confidence: 82%
“…Period effects are of particular importance if research takes a life-span perspective. Taking that very perspective, Borg et al (2017) examined age-related differences in value preferences using data from the European Social Survey 2012 (ESS; N = 50,408) and of a recent German survey on crime prevention ( N = 3,272). As predicted, the authors found that (higher) age was related to a clear shift away from Openness to Change and toward Conservation values.…”
Section: Value Transmission and Value Change In Contextmentioning
confidence: 99%
“…First, it is a reminder of the potential diversity of older adults, as people belonging to the same age group do not necessarily share the same internalized values [40]. Second, the reversal might also be true, as individuals of different cohorts may share the same values [41]. Third, individuals' values change with age [42].…”
Section: The Spanish Socio-cultural and Historical Contextmentioning
confidence: 99%